Speech text of signing ceremony memorandum of understanding (MoU) between between The Centre of Foundation Studies, UiTM Selangor Branch, Dengkil Campus and Albukhary International University / Prof. Datuk Ts. Dr. Roziah Mohd Janor - Mohd Janor, Roziah (2023)
As we move forward, we must continue to recognise the importance of global partnerships in higher education. 5. UiTM and AIU share a common goal of providing high-quality education and research opportunities to students, and this MoU will enable us to achieve that goal by promoting academic and research cooperation between our institutions. 6. Albukhary International University (AIU) is recognised for its excellence in education, research, and community engagement.